Circular RNA CircPPP1CB Suppresses Tumorigenesis by Interacting With the MiR-1307-3p/SMG1 Axis in Human Bladder Cancer - Wang, Feifan; Zhang, Yan; Zhou, Xuejian; Chen, Xianwu; Xiang, Jiayong; Fan, Mengjing; Yu, Yanlan; Cai, Yueshu; Wu, Hongshen; Huang, Shihan; He, Ning; Hu, Zhenghui; et al. (Frontiers in Cell and Developmental Biology, 2021)
Circular RNA (circRNA) is a newly discovered endogenous non-coding RNA (ncRNA), which is characterized with a closed circular structure. A growing body of evidence has verified the vital roles of circRNAs in human cancer. In this research, we selected circPPP1CB as a study object by circRNA sequencing and quantitative real-time PCR (qRT-PCR) validation in human bladder cancer (BC). CircPPP1CB is downregulated in BC and is negatively correlated with clinical stages and histological grades. Functionally, circPPP1CB modulated cell growth, metastasis, and epithelial-to-mesenchymal transition (EMT) process in vitro and in vivo. Mechanically, we performed various experiments to verify the circPPP1CB/miR-1307-3p/SMG1 regulatory axis. Taken together, our results demonstrated that circPPP1CB participates in tumor growth, metastasis, and EMT process by interacting with the miR-1307-3p/SMG1 axis, and that circPPP1CB might be a novel therapeutic target and diagnostic biomarker in human BC.